Порівняння методів моделювання дії вибуху на захисні конструкції - Бісик, Сергій Петрович; Чепков, Ігор Борисович; Васьківський, Михайло Іванович; Корбач, Віктор Григорович; Сливінський, Олексій Анатолійович; Давидовський, Леонід Сергійович; Арістархов, Олег Михайлович (НТУ "ХПІ", 2018)
Представленні результати моделювання дії вибуху на металеву пластину з використанням різних розрахункових методів: LOAD_BLAST; LOAD_BLAST_ENHANCED; Arbitrary Lagrangian Eulerian; Particle Blast Method; Smooth Particle Hydrodynamics, що реалізовані в програмі LS-DYNA. Оцінена адекватність та точність цих методів в залежності від коефіцієнту відстані до вибухової речовини. Наведенні переваги й недоліки кожного методу та рекомендації по їх застосуванню за результатами цього моделювання та досвіду авторів.

The results of simulation of the explosion action on a metal structure using different calculation methods are presented: LOAD_BLAST; LOAD_BLAST_ENHANCED; Arbitrary Lagrangian Eulerian; Particle Blast Method; Smooth Particle Hydrodynamics, which are implemented in the program LS-DYNA. The adequacy and accuracy of these methods are evaluated depending on the distance ratio to the explosive substance. The advantages and disadvantages of each method and recommendations for their use based on the results of this simulation and the experience of the authors of the work are presented.
Comparison of methods for modeling of air blast on protective structures
Keywords: протимінна стійкість; металева пластина; озброення; військова техніка; explosion; mine resistance